Discover answers to your most pressing questions at Westonci.ca, the ultimate Q&A platform that connects you with expert solutions. Get detailed and precise answers to your questions from a dedicated community of experts on our Q&A platform. Explore comprehensive solutions to your questions from a wide range of professionals on our user-friendly platform.

Factorize the following function 36(3x-2)² - 25(2-x)²

Sagot :

The question is given to factorize the expression:

[tex]36\mleft(3x-2\mright)^2\: -\: 25\mleft(2-x\mright)^2​[/tex]

Given that:

[tex]\begin{gathered} 36=6^2 \\ 15=5^2 \end{gathered}[/tex]

Therefore, the expression becomes:

[tex]\Rightarrow6^2(3x-2)^2\: -\: 5^2(2-x)^2​[/tex]

Recall the rule of exponents:

[tex]m^x\cdot n^x=(m\cdot n)^x[/tex]

Hence, the expression can be rewritten to be:

[tex]\Rightarrow\lbrack6(3x-2)\rbrack^2\: -\: \lbrack5(2-x)\rbrack^2[/tex]

Expand the terms in the brackets:

[tex]\begin{gathered} 6(3x-2)=18x-12 \\ 5(2-x)=10-5x \end{gathered}[/tex]

Hence, we have the expression to be:

[tex]\Rightarrow(18x-12)^2-(10-5x)^2[/tex]

Recall the Difference of Two Squares Formula, defined as:

[tex]x^2-y^2=(x-y)(x+y)[/tex]

Hence, we have the expression to be:

[tex](18x-12)^2-(10-5x)^2=\lbrack(18x-12)-(10-5x)\rbrack\cdot\lbrack(18x-12)+(10-5x)\rbrack[/tex]

Simplifying, we have:

[tex]\Rightarrow(18x-12-10+5x)\cdot(18x-12+10-5x)=(23x-22)(13x-2)[/tex]

ANSWER:

[tex]36\mleft(3x-2\mright)^{2}-25\mleft(2-x\mright)^{2}​=(23x-22)(13x-2)[/tex]